Fourth ventricle index: sonographic marker for severe fetal vermian dysgenesis/agenesis. (31st January 2019) - Haratz, K. K.; Shulevitz, S. L.; Leibovitz, Z.; Lev, D.; Shalev, J.; Tomarkin, M.; Malinger, G.; Lerman‐Sagie, T.; Gindes, L.
ABSTRACT: Objective: Prenatal diagnosis of midbrain‐hindbrain (MB‐HB) malformations relies primarily on abnormal size and shape of the cerebellum and retrocerebellar space, particularly 'open fourth ventricle' (4V), the most common indicator of MB‐HB malformations. The aim of this study was to present the fourth ventricle index (4VI), and to evaluate its role as a marker for severe vermian dysgenesis/agenesis in cases without open 4V. Methods: This was a prospective cross‐sectional study of patients with singleton low‐risk pregnancy at 14 + 1 to 36 + 6 gestational weeks presenting between May 2016 and November 2017 for routine ultrasound examination. Axial images of the fetal 4V were obtained and the 4VI was calculated as the ratio between the laterolateral and the anteroposterior diameters. Reference ranges were constructed and retrospectively collected values from 44 fetuses with confirmed anomalies involving severe vermian dysgenesis/agenesis (Joubert syndrome and related disorders, rhombencephalosynapsis, cobblestone malformations and cerebellar hypoplasia) but without open 4V were compared with the normal values. Results: In total, 384 healthy fetuses were enrolled into the study, from which reference ranges were produced, and 44 cases were collected retrospectively. The 4VI in the normal fetuses was always > 1. In affected fetuses, it was always below mean −2 SD and < 1. Conclusions: The 4VI is a sonographic marker for severe fetal vermian dysgenesis/agenesis in the absence of an open 4V. It may be incorporated easily into the routine brain scan; 4VI < 1 indicates a need for dedicated fetal neuroimaging for diagnosis and prenatal counseling. Copyright © 2018 ISUOG. Published by John Wiley & Sons Ltd.